Endovascular treatment or general treatment: how should acute ischemic stroke patients choose to benefit from them the most?. Issue 20 (15th May 2020) - Yang, Weinan; Zhang, Lincheng; Yao, Qigu; Chen, Weiyan; Yang, Weiji; Zhang, Suqing; He, Lan; Li, Hong; Zhang, Yuyan
Abstract: Background: Acute ischemic stroke due to large-vessel occlusion is a leading cause of death and disability, and therapeutic time window was limited to 4.5 hour when treated with intravenous thrombolysis. It has been acknowledged that endovascular treatment (EVT) is superior to general treatment (only medication, including intravenous recombinant tissue plasminogen activator (rt-PA)) in improving the outcome of AIS since 2015. However, the benefits were limited to improvement of functional outcomes and functional independence. Hence, this meta-analysis was conducted to summarize the benefits of EVT for acute ischemic stroke, explore underlying indications of EVT for AIS patients and suggest implications for clinical practice and future research. Methods: A search was performed to identify eligible studies in PubMed, Scopus and Web of Science updated to February 5, 2019. Functional outcomes, the modified Rankin Scale (mRS) 0–1, mRS 0–2, all-cause mortality, symptomatic intracerebral hemorrhage and asymptomatic intracerebral hemorrhage (aICH) at 90 days were selected as outcomes. Data was pooled to calculate the odds ratio (OR) and 95% confidence interval (CI). Heterogeneity, subgroup analysis, sensitivity analysis and publication bias were also performed in this meta-analysis. Results: Eighteen studies comprising 3831 patients were included and analyzed in this meta-analysis. In comparison with general treatment, improved functional outcomes (mRS 0–1: OR = 1.68, 95% CI = 1.43–1.97, inconsistency index [ I 2]  = 57%, P  < .00001; mRS 0–2: OR = 1.78, 95% CI = 1.55–2.03, I 2  = 69%, P  < .00001), reduced risk of all-cause mortality (OR = 0.82, 95% CI = 0.70–0.98, I 2  = 27%, P  = .03) but higher risk of aICH (OR = 1.43, 95% CI = 1.05–1.95, I 2  = 0%, P  = .02) at 90 days were found in AIS patients treated with EVT. Age < 70, National Institutes of Health Stroke Scale ≥20 and maximum delay for invention>5 hours could improve clinical outcomes following EVT. In sensitivity analysis, it showed that 2 studies had a great influence on the pooled ORs. No potential publication bias was found in this meta-analysis. Conclusion: Taken together, EVT, which led to improved functional outcomes and decreased risk of death, is superior to general treatment for AIS patients with age < 70, National Institutes of Health Stroke Scale ≥20 and maximum delay for invention>5 hours. Moreover, it suggests that "with mechanical thrombectomy" is potential favorable factor for improving aICH in comparison with general treatment.